Implementation and Actualization Five Work Cultural Values Ministry af Religion at State Islamic High School, Lumajang District - Muhammad Mudhofar; Agus Salim; Yusuf Wibisono (Jurnal Ilmu Manajemen Advantage, 2022)
Organizational culture will give birth to employee work culture in realizing organizational goals. In 2015 the Ministry of Religion has established five work cultural values ​​as guidelines in the implementation of duties and obligations of employees. The five values ​​of the work culture are integrity, professionalism, innovation, responsibility and exemplary. This research was conducted to determine the implementation and actualization of the five values ​​of work culture at the Lumajang State Aliyah Madrasah. This type of research is descriptive qualitative with data collection through interviews and documentation studies. The results of the study show that the indicators of the five values ​​of work culture have not been fully implemented by employees. Employees and teachers do not understand that since 2015 five work culture values ​​have been launched. The indicator of refusing gratuity is not fully understood as a behavior that must be avoided. Indicators of timely implementation and completion of tasks have been carried out, but the submission or collection of assignments is waiting to be reminded. Indicators provide ideas, breakthroughs and solutions in an inspiring and strategic sense that are the responsibility of madrasah leaders and have not yet developed in employees.